2021
DOI: 10.15252/embj.2020105612
|View full text |Cite
|
Sign up to set email alerts
|

ZSP‐1 is a Z granule surface protein required for Z granule fluidity and germline immortality in Caenorhabditis elegans

Abstract: Germ granules are biomolecular condensates that form in germ cells of all/most animals, where they regulate mRNA expression to promote germ cell function and totipotency. In the adult Caenorhabditis elegans germ cell, these granules are composed of at least four distinct sub-compartments, one of which is the Z granule. To better understand the role of the Z granule in germ cell biology, we conducted a genetic screen for genes specifically required for Z granule assembly or morphology. Here, we show that zsp-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 71 publications
(155 reference statements)
2
32
0
Order By: Relevance
“…Unfortunately, the direct assessment of colocalization between ZNFX‐1 and PID‐2 was thus far hampered by the very close linkage between the PID‐2::eGFP transgene and an available endogenously tagged ZNFX‐1 allele (Wan et al , 2018). Given that Wan et al (2020) show that PID‐2 (named ZSP‐1 by Wan et al) is indeed in Z granules, we did not further pursue PID‐2‐ZNFX‐1 colocalization ourselves.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the direct assessment of colocalization between ZNFX‐1 and PID‐2 was thus far hampered by the very close linkage between the PID‐2::eGFP transgene and an available endogenously tagged ZNFX‐1 allele (Wan et al , 2018). Given that Wan et al (2020) show that PID‐2 (named ZSP‐1 by Wan et al) is indeed in Z granules, we did not further pursue PID‐2‐ZNFX‐1 colocalization ourselves.…”
Section: Resultsmentioning
confidence: 99%
“…The zsp-1 gene is translated in the germline of C. elegans and forms puncta around the germ cell nuclei. Upon more detailed characterization of ZSP-1 localization using stimulated emission depletion microscopy, the authors found that ZSP-1 localized to the exterior of Z granules [ 204 ]. Moreover, proper ZSP-1 localization is critical for maintaining the liquid-like properties of the Z granule.…”
Section: Functional Examples Of Organized Condensatesmentioning
confidence: 99%
“…Interestingly, this finding is reminiscent of the internal organization of P granules, one of the three components in PZM complex. However, ZSP-1 and the P granule surface protein, MEG-3 have very different relationships with their respective condensates [ 84 , 116 , 204 ]. Nevertheless, in future studies, it will be of interest to determine if ZSP-1 and the P granule surface protein, MEG-3, interact in a bridge or node-based network, and whether this network is involved in TEI.…”
Section: Functional Examples Of Organized Condensatesmentioning
confidence: 99%
“…PID-2/4/5 are recently identified factors that affect the structure of Z granules, are required for germ cell immortality, and are similarly required to balance 22G-RNA signals. [38,39] These studies demonstrate a link between Z granules and the biogenesis and inheritance of 22G-RNAs.…”
Section: Introductionmentioning
confidence: 79%
“…[36] Known sub-granules include Z-granules, SIMR foci, and Mutator foci -each containing sets of proteins that refine and resolve processes or steps of small RNA biosynthesis. [37][38][39] C. elegans expresses several classes of small RNAs. [40,41] 21U-RNAs are considered the piRNAs of C. elegans due to their interaction with the germline-expressed PRG-1 Argonaute, the main Piwi-class Argonaute of C. elegans.…”
Section: Introductionmentioning
confidence: 99%